A new Ninox owl from Sumba, Indonesia - Olsen, Jerry; Wink, Michael; Sauer-Gürth, Hedwig (Emu, 2016)
Since the late 1980s ornithologists have reported an unknown Otus owl from the island of Sumba, Indonesia. From a specimen of this unknown owl we analysed the mitochondrial cytochrome b gene in feathers and compared its sequence with those in our data library, which includes most owl genera. A phylogenetic analysis unequivocally places the unknown owl into the Ninox clade. It differs from N. novaeseelandiae and N. scutulata by 8.2 and 9.1% nucleotide substitutions, but our Ninox data set contains few representatives so we cannot define to which other Ninox species it is most closely related. There was no overlap in measurements of body length or mass for this specimen and those of other Ninox known from this region. The call of this new owl was a monosyllabic hoot repeated about every three seconds and quite unlike the repeated ‘cluck-cluck-cluck’ made by the endemic N. rudolfi or the disyllabic notes made by most Ninox, including others in the region. For this new species we assign the common name Little Sumba Hawk-Owl. The conservation status of this owl has yet to be determined, but the species might be threatened and we propose it as Data Deficient.